Prevalence and Determinants of Engagement with Obesity Care in the United States. Issue 5 (6th April 2018) - Stokes, Andrew; Collins, Jason M.; Grant, Bethany F.; Hsiao, Chia‐Wen; Johnston, Stephen S.; Ammann, Eric M.; Berry, Kaitlyn M.; Tong, Cindy; Scamuffa, Robin F.
Abstract : Objective: Medical management of obesity can result in significant weight loss and reduce the burden of obesity‐related complications. This report employs a new conceptual model to quantify engagement with obesity care and associated determinants in the US adult population. Methods: Engagement with obesity care was conceptualized as a cascade comprising 5 successive steps: perceiving oneself as overweight, desiring to lose weight, attempting weight loss, seeking care from a health care professional for obesity, and seeking care from a physician specifically. Results: Among adults with obesity, 7.3% did not perceive themselves as overweight, 1.5% perceived themselves as overweight but had no desire to lose weight, 29.9% wanted to lose weight but did not try in the last year, 51.3% tried to lose weight but did not consult a health professional, and 6.4% sought help for weight loss from a health professional but not a physician, implying that 96.4% of the population with obesity had an unmet need for obesity care. Conclusions: This analysis provides new insight into the most common points along the cascade at which disengagement occurs and can inform efforts to improve uptake of obesity‐related health care services.